1990
DOI: 10.1111/j.1748-1716.1990.tb08834.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter characteristics of small mesenteric arteries from the rat

Abstract: We have studied the neurogenic response of small mesenteric arteries from the rat to evaluate the involvement of possible co-transmitters under various modes of stimulation. Segments of small branches of the mesenteric artery were mounted in a myograph and the intramural nerves were activated with transmural electrical stimulation. A single stimulation of the nerves caused a contraction that was reduced by only 20% in the presence of adrenergic blocking agents (prazosin or phenoxybenzamine), whereas the steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 20 publications
7
54
1
Order By: Relevance
“…In a number of vessels where (i-antagonist resistant responses have been recorded, they have been shown to be due to the activation of P2x-purinoceptors by ATP co-released with NA from sympathetic nerves (von Kugelgen & Starke, 1985;Brizzolara & Burnstock, 1990;Sjoblom-Widfeldt et al, 1990). In the present study, arteriolar constrictions were evoked in response to the exogenous application of ATP, mATP and DADPP.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In a number of vessels where (i-antagonist resistant responses have been recorded, they have been shown to be due to the activation of P2x-purinoceptors by ATP co-released with NA from sympathetic nerves (von Kugelgen & Starke, 1985;Brizzolara & Burnstock, 1990;Sjoblom-Widfeldt et al, 1990). In the present study, arteriolar constrictions were evoked in response to the exogenous application of ATP, mATP and DADPP.…”
Section: Discussionsupporting
confidence: 50%
“…Hirst & Neild (1980;1981) suggested that the xadrenoceptor resistant responses in this vessel were due to the action of NA through a novel y-adrenoceptor. In a number of other arteries cx-adrenoceptor antagonist resistant contractions following sympathetic nerve stimulation have been recorded (Muramatsu et al, 1989;Sjoblom-Widfeldt et al, 1990;Brizzolara & Burnstock, 1990). These are thought to be due to ATP, which is co-released with NA, acting through P2x-purinoceptors because they are abolished following desensitization of P2x-purinoceptors with the stable adenosine 5'-triphosphate (ATP) analogue cxj-methylene ATP (Ramme et al, 1987;Hirst & Jobling, 1989;Evans & Cunnane, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenteric arteries supplying the gastrointestinal tract of rat, guinea pig, rabbit and dog have been shown to be innervated by sympathetic nerves in which ATP is a major cotransmitter with NA [78,79,187,357,411,453,493,528,623,689]. For the sympathetic nerves in the jejunal branches of the rabbit mesenteric artery, like those supplying submucosal arterioles, ATP appears to be the sole transmitter, while NA acts prejunctionally [564].…”
Section: Purinergic Vascular Control In Gutmentioning
confidence: 99%
“…Modulation of ATP release by noradrenaline can only be revealed during nerve stimulation of very low frequencies (0.2±2 Hz) and short duration (10 s) [9,117]. Parallel with what has been described on transmitter release, the neurogenic contractions induced by electrical field stimulation of postganglionic sympathetic nerves within splanchnic vessels are biphasic [16,94,144,154]. In dog [115] and rabbit mesenteric arteries [181], the first component is purinergic in nature, develops rapidly, is transient and predominates at low frequencies (1-2 Hz) of stimulation, whereas the second component is adrenergic, develops after the purinergic one, is more long-lasting and becomes more evident as the frequency of stimulation increases (10 Hz).…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 79%